2009
DOI: 10.1001/archinternmed.2008.505
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Habits and Susceptibility to the Common Cold

Abstract: Background Sleep quality is thought to be an important predictor of immunity and in turn susceptibility to the common cold. This article examines whether sleep duration and efficiency in the weeks preceding viral exposure are associated with cold susceptibility. Methods Participants were 153 healthy men and women volunteers, ages 21–55. For 14 consecutive days, they reported their sleep duration and sleep efficiency (percent of time in bed actually asleep) for the previous night, and whether they felt rested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
337
3
17

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(367 citation statements)
references
References 28 publications
10
337
3
17
Order By: Relevance
“…A prolonged sleep deprivation increases susceptibility to infection in both humans and rodents. 29,36,[73][74][75] In healthy humans, the levels of IL-1b in blood plasma are highest at the onset of sleep. 16,76 This and other evidence, including circadian control of the production of somnogenic cytokines, indicates their involvement in physiological sleep regulation.…”
Section: Relationship Of Protein Fragments To Other Somnogensmentioning
confidence: 99%
See 1 more Smart Citation
“…A prolonged sleep deprivation increases susceptibility to infection in both humans and rodents. 29,36,[73][74][75] In healthy humans, the levels of IL-1b in blood plasma are highest at the onset of sleep. 16,76 This and other evidence, including circadian control of the production of somnogenic cytokines, indicates their involvement in physiological sleep regulation.…”
Section: Relationship Of Protein Fragments To Other Somnogensmentioning
confidence: 99%
“…56,65,66 As described below, these and other inflammatory cytokines can act as somnogens, indicating a major but incompletely understood connection between the immune system and sleep. 4,16,29,31,36,[67][68][69][70][71][72][73][74][75][76][77][78][79] Another potent endogenous somnogen is the PGD 2 prostaglandin, which preferentially induces NREM sleep. 11,28,80,81 The somnogenic activity of PGD 2 is mediated at least in part by the ability of brain-produced PGD 2 to increase the concentration of extracellular adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged bouts of vigorous exercise have been shown to result in transient depression of several white blood cell (leukocyte) functions and it is suggested that such changes create an "open window" of diminished host protection, during which viruses and bacteria can gain a foothold, increasing the risk that infection symptoms will develop 5 . Other factors such as competition 3,4 and psychological stress, lack of sleep 7 , exposure to environmental extremes (e.g. altitude) and malnutrition can also depress immunity 8,9 and lead to increased risk of infection ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep loss can have profound effects not only on supports immune function but upon human performance [5,6,20,22,40]. Many studies indicate that sleep deprivation disrupts cellular immunity [3,7,8,12,14,27,35].…”
Section: Introductionmentioning
confidence: 99%